Rancangan Atap Otomatis Menggunakan Energi Surya Dengan Sensor LDR Berbasis IoT - Nizam Bayu Mahesa (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Weather in Indonesia very often experiences erratic changes because Indonesia has two seasons. Thus, it is difficult to predict rainy and sunny weather in Indonesia. Weather plays an important role in the salted fish industry, one of which is the drying of fish. The main problem is when it rains suddenly, where workers have to transport fish so that they are not exposed to rain water. This process is very ineffective in terms of time or effort. In this research, a system will be designed to make a roof controller automatically. This tool uses a microcontroller coupled with an LDR sensor, which when the sensor does not receive sunlight, the LDR sensor will interpret that it will rain, and then the roof will be closed automatically. When the sensor receives sunlight, the sensor LDR will interpret that the environment is hot, then the roof will open automatically. The LDR sensor will send data to the ESP8266 which then the data will be sent to ThingSpeak in the form of light intensity data and the ESP8266 will command the servo motor to move the roof. In this study, if the light intensity entering the sensor is more than 500, the servo motor will move then the roof will open and if the incoming light intensity is less than 450, the servo motor will move to close the roof. The author uses a microcontroller as an automatic roof controller. To make design this tool the authors made an automatic roof prototype using a microcontroller-based LDR sensor coupled with a servo motor.